Blood products transfusion and retinopathy of prematurity: A cohort study. Issue 3 (11th October 2022) - Uberos, Jose; Fernandez‐Marin, Elisabeth; Campos‐Martínez, Ana; Ruiz‐López, Aida; García‐Serrano, Jose Luis
Abstract: Aim: The aim of the study was to assess the influence of blood product transfusions on the development and severity of retinopathy of prematurity (ROP). Methods: A retrospective cohort study was conducted of very low birth weight (VLBW) newborns with less than 32 weeks gestational age (GA) admitted to the neonatal unit of a tertiary care hospital during the period from 1 January 2008 to 31 December 2021. Data on the degree of ROP and the transfusions received were obtained and analysed. Both univariate and multivariate analyses were performed, by logistic regression. Results: A total of 565 VLBW newborns were recruited, of whom 263 received a red blood cell transfusion prior to 36 weeks corrected GA. The newborns with ROP received significantly more red blood cell transfusions than those not presenting this condition. After adjusting for oxygen therapy and GA, the risk of ROP was found to be 2.77 times higher (95% CI 1.31–5.88) after receiving three or more transfusions, with a 3.95 times higher risk (95% CI 1.40–11.1) of developing severe ROP. Having received the first red blood cell transfusion before 32 weeks corrected GA is associated with an increased risk of ROP (OR 2.18; 95% CI: 1.09–4.36). Conclusion: In VLBW neonates, the number of red blood cell transfusions and their administration before 32 weeks corrected GA are important risk factors for ROP.